CORRELATION BETWEEN ANXIETY AND BREAST MILK PRODUCTION AMONG BREASTFEEDING MOTHERS IN PUBLIC HEALTH CENTER OF JAGIR, SURABAYA - Yurike Septianingrum; Nety Mawarda Hatmanti; Andikawati Fitriasari (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: The low coverage of exclusive breastfeeding in Indonesia is caused by several factors, one of which is anxiety. The mother feels anxious because she is unable to provide enough milk for her baby.Objectives: The purpose of this study is to analyze the correlation between anxiety and breast milk production among breastfeeding mother in Public Health Center of Jagir, Surabaya.Methods: The design of this study was observational analytic with the cross-sectional approach. The study population were all of breastfeeding mothers in Public Health Center of Jagir, Surabaya who met the inclusion and exclusion criteria. The sample of this study was recruited through purposive sampling as many as 67 mothers. Data were collected by using the State Anxiety Inventory Questionnaire and the breast milk production observational sheet. The results of Cronbach Alpha test for the State Anxiety Inventory Questionnaire was .619 and the breast milk production observational sheet was .711. Descriptive statistics and Spearmen Rank Test with significance value less than .05 were used to analyzed data.Results: The results showed: 1) most breastfeeding mothers experienced moderate anxiety (91.04%), 2) some breastfeeding mothers showed smooth milk production (61.19%), 3) There was a correlation between anxiety and breast production in breastfeeding mothers (p = 0.001).Conclusion: The more severe anxiety in nursing mothers, the production of breast milk becomes not smooth. Future studies are expected to analyze other factors that can affect breast milk production in breastfeeding mothers. Keywords: Anxiety, Breast Milk Production, Breastfeeding Mother